Thunder road - whole-body vibration during road cycling, and the effect of different seatpost designs to minimise it - Edwards, P. I.; Holsgrove, T. P. (Journal of Sports Sciences, 2021)
Exposure to whole-body vibration (WBV) increases the risk of low back pain, spinal degeneration, and injury. Cycling can expose participants to WBV, but there are limited data available. This preliminary study quantified WBV in road cyclists in accordance with ISO 2631-1, and determined the efficacy of two seatposts designed to minimise vibration, compared to an aluminium alloy seatpost. Sensors were used to measure the root-mean-squared acceleration (arms), frequency-weighted arms based on an eight-hour reference period (A(8)), vibration dose value (VDV), and transmissibility. Exposures were also calculated using the root-sum-of-squares of the frequency-weighted arms in all three axes (A(8)rss and VDVrss). The mean±95% confidence interval A(8)rss and VDVrss across all tests was 0.58 ± 0.07 ms-2 and 37.19 ± 4.70 ms-1.75 respectively at the saddle, if and 0.49 ± 0.06 ms-2 and 24.31 ± 2.89 ms-1.75 respectively at the lumbar position. Occupational limits were exceeded with all seatposts, and there were no significant differences between them (p > 0.227). Road cycling results in substantial WBV, and there was no evidence that the seatposts designed to minimise vibrations successfully do so. Further research into the effect of cycling conditions and equipment on WBV would be valuable to both the research and cycling communities.